1978
DOI: 10.1037/0003-066x.33.3.284
|View full text |Cite
|
Sign up to set email alerts
|

A thirty-year follow-up of treatment effects.

Abstract: Over 500 men, half of whom had been randomly assigned to a treatment program that lasted approximately 5 years, were traced 30 years after termination of the project. Although subjective evaluations of the program by those-who received its benefits would suggest that the intervention had been helpful, comparisons between the treatment and control groups indicate that the program had negative side effects as measured by criminal behavior, death, disease, occupational status, and job satisfaction. Several possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
1
8

Year Published

1982
1982
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 408 publications
(216 citation statements)
references
References 2 publications
(2 reference statements)
4
203
1
8
Order By: Relevance
“…One of the rst, and one of the best designed, the Cambridge-Somerville study (McCord, 1978(McCord, , 1992Powers &Witmer, 1951), started in the 1930s. Although some of these studies have shown that interventions can have iatrogenic effects (Dishion, McCord, & Poulin, 1999;McCord, 1978), some have shown long-term positive effects (e.g., Hawkins, Farrington, & Catalano, 1998;Olds et al, 1998;Tremblay, Kurtz, Mâsse, Vitaro, & Pihl, 1995;Vitaro, Brendgen, & Tremblay, in press;Weikart & Schweinhart, 1992). However, to my knowledge, none have shown a signi cant long-term impact on the most feared form of aggression.…”
Section: Understanding and Changing The Course Of Developmentmentioning
confidence: 99%
“…One of the rst, and one of the best designed, the Cambridge-Somerville study (McCord, 1978(McCord, , 1992Powers &Witmer, 1951), started in the 1930s. Although some of these studies have shown that interventions can have iatrogenic effects (Dishion, McCord, & Poulin, 1999;McCord, 1978), some have shown long-term positive effects (e.g., Hawkins, Farrington, & Catalano, 1998;Olds et al, 1998;Tremblay, Kurtz, Mâsse, Vitaro, & Pihl, 1995;Vitaro, Brendgen, & Tremblay, in press;Weikart & Schweinhart, 1992). However, to my knowledge, none have shown a signi cant long-term impact on the most feared form of aggression.…”
Section: Understanding and Changing The Course Of Developmentmentioning
confidence: 99%
“…3 This is not the only intervention to find no beneficial effects or unanticipated negative effects on participants. The well-known randomized, experimental trial of the communitybased treatment program Cambridge-Somerville Youth Study, whose objective was to prevent delinquency, found that youths in the treatment group were more likely to be rearrested for crimes and have other negative impacts on physical and psychological health compared to youths in the control group in the long-run (McCord, 1978 and1992). The intervention was targeted to boys ages 5 to 13, and children in the treatment group received an individual counselor who visited the family around twice a month for five years and were referred to or received services in a variety of areas: tutoring, medical, psychiatric, summer camps, Boy Scouts, YMCA, or other community programs.…”
Section: Alternative Explanations For Unanticipated Negative Effecmentioning
confidence: 99%
“…Il est à noter qu'il ne s'agit pas d'un cas isolé. La Cambridge-Somerville Youth Study (CSYS) qui avait comme objectif de prévenir la délinquance chez les jeunes à risque est un exemple classique d'effet iatrogène (McCord, 1978). Les jeunes qui ont pris part à cette intervention dans les années quarante présentaient plus de problèmes d'ajustement 30 ans plus tard que ceux du groupe contrôle.…”
Section: Suivi 2 Ans Suivi 3 Ansunclassified